Justice and rights Christian and Muslim perspectives : a record of the fifth "Building bridges" seminar held in Washington, D.C., March 27-30, 2006 - Ipgrave, Michael (Washington, DC : Georgetown University Press, 2009)
"A record of the fifth "Building bridges" seminar held in Washington, D.C., March 27-30, 2006."
Ruler and the ruled in Islam : a brief analysis of the sources / Mohammad Hashim Kamali -- Biblical perspectives on divine justice and political authority / Ellen F. Davis -- Scriptural texts. Two Psalms / Ellen F. Davis -- r Timothy J. Winter -- Religious orthodoxy and religious rights in medieval Islam : a reality check on the road to religious toleration / Vincent J. Cornell -- Une Foi, une loi, un roi : political authority and religious freedom in the West, from Constantine to Jefferson / John Langan -- Traditional texts -- Letter of St. Augustine / Rowan Williams -- Response of ibn Lubb -- r
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christianity and justice -- Congresses; Islam and justice -- Congresses; Human rights -- Religious aspects -- Christianity -- Congresses; Human rights -- Religious aspects -- Islam -- Congresses; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Electronic books